The Structure of the Contemporary International Political System between Pluralism and Unipolarism: Study of the Theory - السحاتي خالد (Dirasat in Economics and Business, 2019)
This theoretical study deals with the theme of "The Structure of the Contemporary International System between Pluralism and Unipolarism". This study is divided into four main axes. The first is the concept of structure of the international system. Second: theoretical trends in the study of the structure of the international political system, Third: determinants of the structure of the international system, the fourth axis: the nature of the international system and the changes that have occurred, The study of the international system is concerned with the structure of power, authority and influence, the types of conflicts and the methods of resolution used by international players to achieve their goals, The entire structure of the international system is determined by the pattern of power distribution among the major Powers at its peak, which in turn determines the distribution of polarity in the international system, on the nature of the structure of the international system at this stage, many trends emerge: a unipolar system, the events of September 2001 provided more indications that the emergence of the new world order, another trend that is a multipolar system, a school in America has come to believe that the next international order will be based on multilateralism. The summit of this international system will be occupied by major states, not a single superpower, Third direction: sees international non-polar system ", which means moving towards a world not dominated by one power, and two dominant or two great state, but dozens of actors on the international stage who possess different types and spheres of force, It appears from the presentation of these trends that the determination of the structure of the international system at the current stage has witnessed a great controversy among scholars, while some believe that the system of polarity is the system that will develop the future of the international system towards it, it may be consensual or competitive.